IMPLEMENTATION THE APPLICATION OF LEARNING GUIDENCE SERVICES THE STRENGTHENING OF DISCIPLINE AND ACHIEVEMENT (Studies in Grade VIII SMP N 02 Lebong). - Febi Fetrayani; Turdjai Turdjai (UNIB Press, 2019)
The purpose of this study is to describe the application of learning guidence service in orderto improve the students’ discipline and achievement in class VIII SMP Negeri 02 Lebongin the school year 2018/2019. The research used action research class method (class room action research). The subjects of this study were 30 students. Data collection techiques in this study were observation and documentation. Collecting data in this study were obtined using direct observation and interviews, in IPA subject learning. The data is analyzed using qualitative and quantitative and processed using t formula. The test resnt of this study concluded that’s the students’ discipline and achievement have increased significanty through the application of learning guidance services.